Determination of Ownership Structure, Profitability, and Liquidity on Dividend Policy in Companies Listed on the JII - Maftuh Al husna, Muhammad Zidan; Yoga, Ika (University of Darussalam Gontor, 2024)
This study analyzes the effect of ownership structure, profitability, and liquidity on dividend policy in 18 companies listed on the Jakarta Islamic Index (JII) for the 2019-2023 period.Secondary data in the form of company financial reports obtained from the Indonesia Stock Exchange were analyzed using panel data regression with Eviews software. The findings indicate that managerial ownership (MNRG) exerts a negligible influence on dividend policy (DPR), given the negligible proportion of managerial shares relative to public shares.Conversely, Return on Assets (ROA) demonstrates a positive and significant relationship with DPR, suggesting that higher profitability leads to increased dividend distribution likelihood. The study further found that Net Profit Margin (NPM) exerts no significant influence on DPR, suggesting that net profit is predominantly allocated to support the company's operational needs.The Current Ratio (CR) was found to have a positive and significant effect on DPR, indicating that a higher liquidity level in the company corresponds with its greater capacity to pay dividends. Consequently, this study validates that profitability and liquidity emerge as the predominant factors influencing dividend policy in companies listed on the Jakarta Islamic Index (JII) during the 2019-2023 period.